(untitled) (Politeja, 2025)
INTERNATIONAL COCAINE TRAFFICKING AND ITS CONSEQUENCES FOR AFRICAN SOCIETIES AND STATES According to data of the United Nations Office on Drugs and Crime (UNODC), there has been a significant increase in cocaine production and in profits from its sale in recent years. This situation significantly affects security issues and has a multi-faceted impact on the societies of many regions, including Africa. It is estimated that 30% of cocaine transport to Europe takes place through the West and Central African region. The amount of cocaine that reaches South Africa and East Africa via the port of Santos in Brazil is also increasing. The African continent is increasingly becoming not only an area through which drugs are transported but also an important destination market. According to the UNDOC estimates, in 2021, about 11% of all cocaine consumers came from Africa. Factors that contribute to the development of the illegal cocaine trade include growing demand, certain profit, weak state institutions in transit countries, limited control over the territory and a high level of corruption. The aim of this article is to indicate the causes of the increasing illegal cocaine trade in recent years and to present the consequences of this phenomenon for the inhabitants of the African continent.